High summertime aerosol organic functional group concentrations from marine and seabird sources at Ross Island, Antarctica, during AWARE - J. Liu; J. Dedrick; J. Dedrick; L. M. Russell; G. I. Senum; J. Uin; C. Kuang; S. R. Springston; W. R. Leaitch; A. C. Aiken; D. Lubin (Atmospheric Chemistry and Physics, 2018)
Observations of the organic components of the natural aerosol are scarce in Antarctica, which limits our understanding of natural aerosols and their connection to seasonal and spatial patterns of cloud albedo in the region. From November 2015 to December 2016, the ARM West Antarctic Radiation Experiment (AWARE) measured submicron aerosol properties near McMurdo Station at the southern tip of Ross Island. Submicron organic mass (OM), particle number, and cloud condensation nuclei concentrations were higher in summer than other seasons. The measurements included a range of compositions and concentrations that likely reflected both local anthropogenic emissions and natural background sources. We isolated the natural organic components by separating a natural factor and a local combustion factor. The natural OM was 150 times higher in summer than in winter. The local anthropogenic emissions were not hygroscopic and had little contribution to the CCN concentrations. Natural sources that included marine sea spray and seabird emissions contributed 56 % OM in summer but only 3 % in winter. The natural OM had high hydroxyl group fraction (55 %), 6 % alkane, and 6 % amine group mass, consistent with marine organic composition. In addition, the Fourier transform infrared (FTIR) spectra showed the natural sources of organic aerosol were characterized by amide group absorption, which may be from seabird populations. Carboxylic acid group contributions were high in summer and associated with natural sources, likely forming by secondary reactions.